2019
DOI: 10.1042/bsr20181476
|View full text |Cite|
|
Sign up to set email alerts
|

LDH-A promotes malignant behavior via activation of epithelial-to-mesenchymal transition in lung adenocarcinoma

Abstract: Lactate dehydrogenase A (LDH-A) is a key enzyme during glycolysis, which increases the synthesis of related proteins and has elevated activity in cancer cells. The role of LDH-A in lung adenocarcinoma (LUAD) progression was investigated in the present study. Expression levels of LDH-A were assessed in LUAD samples, and the relationship between LDH-A expression status and the prognosis of LUAD patients was confirmed. The effect of LDH-A on proliferation, invasion, migration, and colony formation of cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 25 publications
1
47
1
Order By: Relevance
“…Hence, altered expression of LDHC could be involved in maintaining an alternative energy source by contributing to the metabolic switch in cancer cells. In addition, increased LDHA and decreased LDHB expressions facilitate tumor formation and progression through remodeling of the tumor microenvironment, increasing proliferation, and inducing epithelial-to-mesenchymal transition, cell migration and invasion, and angiogenesis [10][11][12][13][14][15][16][17][18][19][20]. In line with this, two studies to date demonstrate that enhanced expression of LDHC induces epithelial-to-mesenchymal transition, matrix metalloproteinase-9 (MMP9) expression and promotes cancer cell migration and invasion [7,21].…”
Section: Introductionmentioning
confidence: 81%
“…Hence, altered expression of LDHC could be involved in maintaining an alternative energy source by contributing to the metabolic switch in cancer cells. In addition, increased LDHA and decreased LDHB expressions facilitate tumor formation and progression through remodeling of the tumor microenvironment, increasing proliferation, and inducing epithelial-to-mesenchymal transition, cell migration and invasion, and angiogenesis [10][11][12][13][14][15][16][17][18][19][20]. In line with this, two studies to date demonstrate that enhanced expression of LDHC induces epithelial-to-mesenchymal transition, matrix metalloproteinase-9 (MMP9) expression and promotes cancer cell migration and invasion [7,21].…”
Section: Introductionmentioning
confidence: 81%
“…LDHA (lactate dehydrogenase A), as a crucial enzyme of energy metabolism, is elevated in various cancers compared with inormal tissues. Previous studies showed that LDHA could promote tumor cells proliferation, invasion, migration, tumor progression, and metastasis, and might be a potential therapeutic target [25][26][27][28][29]. MELTF, also known as MAP97, MTf (Melanotransferrin), or MTF1 (metal regulatory transcription factor 1), as an iron (Fe) binding transferrin homolog, is mainly expressed in melanoma and is low expression in noncancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…LDHA (lactate dehydrogenase A), as a crucial enzyme of energy metabolism, is elevated in various cancers compared with normal tissues. Previous studies showed that LDHA could promote tumor cells proliferation, invasion, migration, tumor progression, and metastasis, and might be a potential therapeutic target [25][26][27][28][29]. MELTF, also known as MAP97, MTf (Melanotransferrin), or MTF1 (metal regulatory transcription factor 1), as an iron (Fe) binding transferrin homolog, is mainly expressed in melanoma and is low expression in noncancerous tissues.…”
Section: Discussionmentioning
confidence: 99%